Choice Of Tactics of Surgical treatment of Syndactyly of the Hand in Children - Salomov Sh.N; Aliev Kh.M; Rakhmanov R.R (Peerian Journals Publishing, 2022)
This article deals with to study the results of surgical treatment of syndactyly of the fingers of the handing children in a comparative aspect
Keywords: Hand; Surgical Treatment; Syndactyly